Analytical Solution of the Ginzburg-Landau Equation (European Journal of Pure and Applied Mathematics, 2022)
In this paper, we will construct the solution of the Landau-Ginzburg equation by the Adomian decomposition method. This method avoids linearization of space and discretization of time, it often gives a good approximation of the exact solution.
Keywords: Adomian method; Ginzburg-Landau equation